(untitled) (Iter, 2022)
The second discourse of Sócrates in the Phaedrus succeeds in connecting its main theme M ith the previous two discourses -united through the use of the dual- by being an offering o f compensation: so eros becomes finally the core of the three discourses. In this article eros is analysed in its relation to the space of the universe and its capacity to enhance. consequently. the perception of time in man ’s soul. In the se circumst andes, love connects the hither o f this sensible Morid with the thither of the heavens as representaron of the inteligible, and becomes transformed in a transcendent power of spiritual ascent.